Urban Community Engagement to Reduce and Prevent Food Waste at Household Level - Whisnu Febry Afrianto; Taufiq Hidayatullah; Laeli Nur Hasanah; Rivandi Pranandita Putra; Rindang Diannita; Ratih Anggraini (International Journal Of Community Service, 2021)
Indonesia faces a food waste problem, particularly at the household level. Food waste causes negative impacts on several aspects such as environment, society, and economy. Ironically, at the same time, Indonesia also has a serious hunger problem. Through community development programs, we aimed to empower households in recycling their food waste by eco enzyme and their awareness through an online challenge. Eco enzyme is an affordable and useful method to recycle food waste being a liquid product with many benefits such as insect repellent, organic fertilizer, general cleaner, air purifier, and laundry cleaner. The total participants of the eco enzyme workshop were 57 people. On the other hand, through an online campaign #MelawanFoodWate, 101 users took action to be conscious customers in shopping behavior. These activities were in collaboration with several stakeholders to ensure the success of the program. These programs can be considered an initiation to develop Food Smart City that focuses on the community-based movement and circular economy.